Clinical Phenotype and Microvascular Dynamics of Subjects with Endothelial Dysfunction as Assessed by Peripheral Tonometry. (April 2016) - Venturi, Elena; Pinnola, Silvia; Morizzo, Carmela; Boldrini, Beatrice; Rossi, Monica; Trifirò, Silvia; Tricò, Domenico; Natali, Andrea; ,
Abstract: Objective: To evaluate the characteristics and the determinants of ED, as measured by PAT. Methods: We measured basal and post‐ischemic digital pulse amplitude (EndoPAT ® ) in a mixed outpatient population of 206 diabetic and 101 non‐diabetic subjects, of whom 50% with clinically manifest CVD, undergoing to an extensive clinical, biochemical, and vascular phenotype characterization. Results: The major characteristics of ED (tertile 1 vs 3), in addition to lower post‐ischemic vasodilatory reserve (34 vs 203%), were a 3‐fold higher baseline pulse amplitude and a delayed (60 second) peak response. The main determinant of this response was the baseline pulse amplitude (St β  = −0.59), which in turn was influenced by age (St β  = 0.13), central obesity (St β  = 0.27) and inversely by HDL cholesterol (St β  = −0.17), and systolic blood pressure (St β  = −0.19). No association was observed with cardiovascular risk factors, previous cardiovascular event or extent of atherosclerosis (ABI and IMT, PWV). Most of the variability in baseline pulse amplitude remained unexplained ( r 2  = 0.14). Conclusions: ED, as detected by PAT in a population enriched with subjects at risk for CVD neither reflects the burden of classical risk factors (under treatment) nor the severity of atherosclerosis. Aside from central obesity and HDL cholesterol, most of the factors responsible for this ED remain unknown.